The Effect of Haryani Leadership Model Training (Harmonious, Adaptive, Responsive, Confident, Authentic, Nurturing, Integrative) on Communication Effectiveness and Nurses’ Performance - Sri Haryani Saraswati; Fery Agusman; Sonhaji Sonhaji (Jurnal Ners, 2026)
Effective communication and nurses’ performance are critical determinants of healthcare service quality in hospital settings. The HARYANI Leadership Model was developed as an innovative framework to enhance both communication effectiveness and nursing performance. This study aimed to examine the effect of HARYANI Leadership Model training on communication effectiveness and nurses’ performance at Columbia Asia Special Surgical Hospital Semarang. This research employed a quantitative approach with a quasi-experimental non-equivalent control group design. A total of 58 nurses were recruited using purposive sampling, comprising 29 participants in the intervention group and 29 in the control group. The intervention group received 40 hours of HARYANI Leadership Model training over a two-week period, while the control group received no intervention. Data were collected using a 51-item communication effectiveness questionnaire and a 42-item nurses’ performance questionnaire. Statistical analyses included paired t-tests, Wilcoxon signed-rank tests, Mann–Whitney U tests, and ANCOVA for multivariate analysis. This study received ethical approval from the Research Ethics Committee of Universitas Karya Husada Semarang (No. 079/KEP/UNKAHA/LPPM/III/2026). The findings demonstrated a substantial increase in communication effectiveness scores in the intervention group (130.14 to 213.90; p = 0.000), compared to a minimal increase in the control group (123.59 to 125.52; p = 0.002). Similarly, nurses’ performance scores in the intervention group improved significantly (91.14 to 170.31; p = 0.000), whereas the control group showed only slight improvement (90.28 to 93.45; p = 0.000). Between-group comparisons revealed statistically significant differences (p < 0.05). The effect sizes were notably large (Cohen’s d = 5.53 for communication effectiveness and 5.59 for performance). Multivariate analysis indicated that demographic variables did not significantly influence the outcomes (p > 0.05). In conclusion, the HARYANI Leadership Model training significantly enhances communication effectiveness and nurses’ performance, suggesting its potential as an effective strategy for strengthening nursing leadership and improving healthcare quality.